ANALISIS KEBIJAKAN PEMANFAATAN SUMBERDAYA DANAU YANG BERKELANJUTAN (STUDI KASUS DANAU MANINJAU SUMATERA BARAT) - Asnil Asnil; Kooswardhono Mudikdjo; Soedodo Hardjoamidjojo; Ahyar Ismail (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2013)
This study aims to formulate policies to preserve environment resources functions related to the use of lake. Descriptive method with survey techniques through observation is used to achieve those objectives, in-depth interviews with those who understand the problem. Analysis of the data is done through three lines of activity simultaneously, which are data reduction, data presentation, and conclusion.